Effects of high intensity-interval training on cardiovascular risk, body mass index and metabolic markers in healthcare workers: Efecto de entrenamiento por intervalos de alta intensidad sobre riesgo cardiovascular, índice de masa corporal y marcadores metabólicos en personal de salud - Gracida Hernandez, Alejandro D. (2022)
Background and Objectives: The obesity epidemic in Mexico has caused a health crisis. This places great importance in the identification of useful methods to manage it across all populations. In this present study we evaluate the effect of high intensity interval training in healthcare workers. Materials and Methods: An intervention was carried out that consisted in 60 sessions of high intensity interval training during a 12 week period aimed at health care workers working at the General Hospital in Montemorelos, Mexico. Variables regarding body composition, cholesterol and arterial blood pressure were evaluated for each individual both before and after the intervention. Pearson coefficients were estimated between the initial and final values. Results: 8 participants were included, 55.6% men aged 32.8 ± 10.9 years with a BMI of 31.69 ± 2.9. A statistically significant difference was found between the initial and final values ​​of weight, BMI, total cholesterol, mean arterial blood pressure,  and cardiovascular risk at 10 years. Conclusions: These results reveal a significant decrease in our variables related to obesity in healthcare workers after a HIIT intervention in an uncontrolled setting. We recommend the further implementation of similar studies with greater sample size, intensity and duration to target obesity which is the root cause of chronic non-communicable diseases. Further studies are required to confirm the effect of this intervention in the prevention, treatment of obesity in health care workers and to describe its long term effects.